ANALISIS KEBUTUHAN AIR BERSIH DI WILAYAH KECAMATAN MADURAN KABUPATEN LAMONGAN - Agus Setiawan; endang suciati; Choirul Anam (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2023)
Water is a water resource that is indispensable for living things both to meet their needs and to sustain life naturally. The higher a person's standard of living, the higher the demand for water. The population of Maduran Subdistrict continues to increase from year to year, which has an impact on increasing water demand. This study aims to calculate the water demand of Maduran Subdistrict for 2032 with 10 year projection. In this study, the projection of water demand is based on primary and secondary data. The projection of water demand for Maduran Subdistrict uses 2 analysis methods, namely the arithmetic method and the geometric method. From the results of the analysis obtained that the total population growth of Maduran Subdistrict in 2032 is 38,761 people. Based on this population, the clean water demand of Maduran Sub-district in 2023 is 52.22 L/dt. While the maximum daily water demand is 57.44 L/dt, the current water availability can serve until 2032.